If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2x = 12 + 7x Solving 3 + -2x = 12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 3 + -2x + -7x = 12 + 7x + -7x Combine like terms: -2x + -7x = -9x 3 + -9x = 12 + 7x + -7x Combine like terms: 7x + -7x = 0 3 + -9x = 12 + 0 3 + -9x = 12 Add '-3' to each side of the equation. 3 + -3 + -9x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -9x = 12 + -3 -9x = 12 + -3 Combine like terms: 12 + -3 = 9 -9x = 9 Divide each side by '-9'. x = -1 Simplifying x = -1
| 4a(3a-5b)= | | 5x^2+29-6= | | 5x-y=24 | | -6/7x+15=-33 | | 26x+21=32x-9 | | 3x^2+10x=32 | | 1/9y=-7 | | -4(y-9)=-10(2-y) | | x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 | | 19+0+(-9)= | | 6/18+3/19 | | 8/11-4/15 | | 4/9+m=20 | | y=-5x^2+30t+2 | | 2*3*4*5= | | 3x-23=1-4x | | 4/16+2/13 | | 4y+8x=48 | | 3x-2(x+4)=-1 | | 14/15-4/12 | | 5x-11=-11 | | 3/4x+2/9-3/7 | | -4x-21=3x+7 | | 7/20+3/9 | | 2450:345= | | 2-1/2(4x+6)=5x-1 |